Characterization of pediatric patients with asthma treated in a health center of Fortaleza - Silva, Sabrina Ferreira da; Monte, Alana Santos; Costa, Camila Chaves da; Joventino, Emanuella Silva; Gomes, Ana Lúcia Araújo; Ximenes, Lorena Barbosa (Rev Rene, 2011)
The aim of this study was to characterize the profile of pediatric patients with asthma enrolled in the “Programa of Atenção Integrada à Criança com Asma”; examine associations between asthma attacks, presence of animals in the household and occurrence of breastfeeding. It is a retrospective, documental and quantitative study that examined 152 asthmatic children of the program. Most of the children in the study were male (n=91; 59.9%) and were aged more than five years (n=80; 53%), with homes of four residents (n=45; 39.8%) with 53 (34.2%) smokers. There were animals in the residence of the majority of the children who had fewer than two (n=35; 33%) and more than two (n=9; 8.5%) asthma attacks a week. It was perceived the occurrence of asthma among children who received breast milk (n=41; 34.4%). We pointed out the importance of the program for children with asthma to promote children’s health.